The Role And Objectives Of A Social Worker In Poland, In Work With A Family With Numerous Problems, Including A Family With An Untreatable Child - Zdebska, Ewelina (European Scientific Journal, ESJ, 2016)
A contemporary Polish family contends with various problems which negatively influence on its structure, stability and quality of mutual relations. At present, it may be observed that there is an increasing number of families which demand help, support and care, especially families with the low economic status, but also families with a disabled child, including an untreatable one. In 2010, in Poland there were 1 375 541 with the number of 3 624 223 members in the families that were covered with help. PHelp was given to those families mainly due to poverty, unemployment, disability, prolonged or serious illness as well as helplesness in childcare issues and housekeeping (the Annual Report of the Ministry of Labour and Social Policy for 2012). This fact indicates that there is a strong demand for a professional support for the families. A social worker acts for individuals, families, groups and the social environments, that are in a difficult situation. It enables or facilitates accomplishment of aspirations and aims in life. It also strengthen capabilities of the social groups, persons, families to solve own problems and manage independently. In the families with an untreatable child, a social worker plays a special role. He or she is a a driving force of changes in the family as well as is a foundation of multifaceted help and support.